Impact of 2018 ASCO/CAP guidelines on HER‐2 reporting categories of IHC and reflex FISH in breast cancer. Issue 11 (31st August 2020) - Pasricha, Sunil; Menon, Vidya; Gupta, Gurudutt; Kamboj, Meenakshi; Sharma, Anila; Durga, Garima; Tripathi, Rupal; Batra, Ullas; Jajodia, Ankush; Koyyala, Venkata Pradeep Babu; Agrawal, Chaturbhuj; Doval, Dinesh C.; et al.
Abstract: Human epidermal growth factor receptor 2 (HER‐2) is an established prognostic and predictive biomarker for breast cancer. To ensure accuracy and uniformity for HER‐2 testing, ASCO/CAP published guidelines in 2007 which were updated in 2013 and recently in 2018. In this first study from Indian Oncology center, we evaluated the impact of 2018 ASCO/CAP guidelines. We found a substantial decrease in equivocal IHC cases ( P ‐value < .00001). On reclassification, a total of 5.6% cases from equivocal and positive categories (2013 guidelines) shifted to the negative FISH result category ( P ‐value < .0001), with adoption of 2018 guidelines and eliminated the double equivocal cases.